PP-verbs: The phenomenon of obligatory Ps (in Hebrew) - Botwinik, Irena (Lingua, 2013)
⿢Focusing mainly on Hebrew, the paper develops a principled account as to the occurrence and function of P with PP-verbs.⿢PP-verbs are claimed to have an underspecified internal θ-role, rendering them incapable of Case-checking.⿢The P in PP-verb constructions is argued to check the Case of its DP complement, rather than to assign it a θ-role.⿢The paper provides evidence for the status of P as an independent syntactic head, projecting a thematically licensed PP. The paper focuses on Hebrew verbs whose internal argument is realized obligatorily as a PP, rather than a DP (PP-verbs) and develops a principled account, as to the occurrence of the PP and the function of P with these verbs. The main claim advanced in the paper, The Underspecification Hypothesis, couched in the Theta System framework (Reinhart, 2002), defines these verbs as having an underspecified internal θ-role, rendering them incapable of Case-checking. Addressing the semantic and syntactic consequences of ⿿underspecification⿿, I illustrate the semantic effects of the ⿿fully specified⿿/⿿underspecified⿿ distinction, and argue that the role of P in PP-verb constructions, unlike in locative constructions, is to check the Case of its DP complement, rather than to assign it a θ-role. Consequently, I provide evidence for the status of P as an independent syntactic head, projecting a thematically licensed PP. Finally, I discuss the proposal from a cross-linguistic perspective, using the variation attested between Hebrew PP-verbs and their Russian and English counterparts, and suggest specific sources for the observed cross-linguistic variation.